THE DANCE TESHKOTO (THE HARD ONE) – A SYNONYMUS OF A HARD DANCE FROM THE TYPE OF LESNOTO (THE EASY ONE) (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
Why Teshkoto (the hard one) as a synonym for a dance like Lesnoto (the easy one)? No matter how paradoxical it sounds, there are certain indicators that indicate and can support this claim. In this text we will look at some of these indicators, such as ethnochoreological features of Teshkoto and Lesnoto, the structure of the dance pattern, the style and the manner of performing the dance. We will also try to make a comparison between the two dances through which we will try to clarify the mentioned phenomenon.